2020
DOI: 10.21037/atm-20-5438
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol enhances the anti-tumor effects of metformin via suppressing epithelial-mesenchymal transition in triple-negative breast cancer

Abstract: Background: Triple-negative breast cancer (TNBC) is a severe disease with a high mortality rate.Metformin has been found to possess anti-tumor properties. Curcumol, an active ingredient extracted from curcuma, exerts the protective effect in TNBC cells through inducing apoptosis. However, the effects of curcumol combined with metformin on the treatment of TNBC have yet to be fully established.Methods: TNBC cells MDA-MB-231 and MDA-MB-468 cells were used in the study. TNBC cells were treated with curcumol and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…As shown in our present study, curcumol inhibits MDR in CRC. Consistent with our results, curcumol has been reported to inhibit Wnt/β-catenin signaling in triple-negative breast cancer and lung adenocarcinoma ( 53 , 54 ). Importantly, aberrant Wnt/β-catenin signaling plays a critical role in the development and progression of various human malignancies, and mutations in this pathway’s components are defining CRC features ( 30 , 55 ).…”
Section: Discussionsupporting
confidence: 92%
“…As shown in our present study, curcumol inhibits MDR in CRC. Consistent with our results, curcumol has been reported to inhibit Wnt/β-catenin signaling in triple-negative breast cancer and lung adenocarcinoma ( 53 , 54 ). Importantly, aberrant Wnt/β-catenin signaling plays a critical role in the development and progression of various human malignancies, and mutations in this pathway’s components are defining CRC features ( 30 , 55 ).…”
Section: Discussionsupporting
confidence: 92%
“… 12 The fibrosis mediated by fibroblasts originating from endothelial cells contributes to the pathological process of DCM, as has been reported previously. 11 The inhibition for EndMT/EMT by metformin has been reported in several studies, 35 , 36 while the action by SGLT2 inhibitors is still unclear. Our study represents the first to investigate how dapagliflozin affects EndMT and fibroblasts and to thoroughly investigate its antifibrotic mechanism of action.…”
Section: Discussionmentioning
confidence: 98%
“…Curcumenol has a variety of pharmacological and biological activities, including antitumor activity, treatment of nerve and mental diseases, and antiliver fibrosis [ 42 44 ]. Studies confirmed that curcumenol has antitumor effects on gastric cancer, colorectal cancer, and breast cancer [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%